Experimental characterisation of rotor noise in tandem configuration - Alper Celik (Applied Acoustics, 2024)
This paper presents a comprehensive investigation into the noise radiation characteristics of two rotors in a tandem configuration. Through an extensive experimental campaign, the study explores the effect of the separation distance between two rotors on the noise directivity patterns, spectral characteristics and temporal features of the radiated noise under both hovering and edge-wise flight conditions. The directivity patterns of the overall sound pressure level obtained from the polar and side arrays demonstrate a dependence on the separation distance and advance ratio. Spectral characteristics elucidate the influence of separation distance on tonal and broadband energy content. While the high-frequency broadband noise increases for both hovering and edge-wise flight similarly, the low-frequency broadband energy strongly depends on the advance ratio and the rotor separation distance. The results reveal a distinct envelope in the design space, where the radiated broadband noise for tandem configurations can be minimized, offering potential insights for noise reduction strategies. Additionally, the wavelet analysis for tandem configurations reveals that the emitted noise at the first and second blade passing frequency is strongly intermittent with amplitude modulation, which shall be considered for annoyance perception.